Idiopathic Focal Osteonecrosis of T9 Vertebral Body Mimicking a Malignant Tumor: A Case Report - Arvind G Kulkarni; Shankargouda Patil; Aniruddh Agrawal; Sunil Chodavadiya; Priyambada Kumar (Journal of Orthopaedic Case Reports)
Introduction: Occurrence of a focal lytic lesion which is “hot” on positron emission tomography (PET) scan is presumed to be neoplastic until proven otherwise. Focal osteonecrosis of vertebral body (VB) without collapse is a rare entity with sparse literature available. Case Report: A focal osteolytic lesion in a patient with a history of breast carcinoma, in remission, thought to be metastatic lesion on magnetic resonance imaging and PET-computed tomography (CT), with an inconclusive CT-guided biopsy, was found to be osteonecrosis on histopathology of aggregates of tissue obtained from the T9 VB during open surgery. Conclusion: Osteonecrosis without a VB collapse is a rare diagnosis, but should be considered a differential when examining suspected metastatic lesions in VB.